ANALISIS PERUBAHAN TOPOGRAFI BUKAAN TAMBANG TERBUKA MENGGUNAKAN DATA FOTOGRAMETRI BERBASIS UAV (Studi Kasus Pada PT. Sumber Swarna Pratama, Kecamatan Petasia, Kabupaten Morowali Utara, Sulawesi Tengah - adidayan pratama; Ruth Bunga Ranggu; Zulfahmi (Fakultas Teknik UPRI, 2026)
Topographic changes in open-pit mining areas occur rapidly due to overburden removal and ore extraction activities. These changes require an efficient monitoring method capable of providing fast, accurate, and reliable data to support production control, safety, and environmental management. This study aims to analyze topographic changes in an open-pit mining area using Unmanned Aerial Vehicle (UAV)-based photogrammetry. Data acquistion was carried out using a UAV at a flight altitude of 120 meters with 80% overlap and 70% sidelap. The capture images were processed using Agisoft Metashape to generate orthomosaic and Digital Elevation Model (DEM), then analyzed using ArcGIS and Surpac to calculate changes in area and material volume. The results show that mining area increased from 4.8 hectares to 5.2 hectares within one month. The volume calculation indicates a cut value of 52,757.44 m3 and a fill value of 16,774.11 m3, with a net change -35,983.30 m3. Based on these results, UAV photogrammetry is proven to be effective in monitoring topographic changes in mining areas in a fast, accurate, and efficient manner compared to conventional surveying methods.